Functional characterization of gibberellic acid related genes from oil palm in Arabidopsis thaliana for potential role height regulation - Abdul Halim, Muhamad Afiq (2017)
Oil palm is the most important commodity crop in Malaysia with a total planted area of 5.74 million hectares. In general, the economic life of the oil palm is associated with the stature of the tree. At maturity, oil palm trees commonly reach over 15 meters in height making harvesting a challenge as fruit bunches may weigh over 20 kg and become damage as the bunches fall to the ground hence reduce the quality of fresh fruit bunch (FFB). Height regulation in plant is commonly associated with gibberellic acid (GA), therefore study of genes related to GA biosynthesis and signaling will improve our understanding on height regulation mechanism in oil palm. Thus, the main objective of the research was to isolate GA-related genes from the oil palm (Elaeis guineensis) and characterize their functions in order to study height regulation in oil palm. Due to oil palm long life cycle, it is difficult to study the gene function in vivo, therefore functional characterization of the genes was conducted in heterologous system using model plant Arabidopsis thaliana. Three GA-related genes, EgGA20ox, EgGA2ox and EgGAI were isolated from leaf tissue of clonal oil palm treated with paclobutrazol (GA inhibitor). EgGA20ox and EgGA2ox genes expression were affected by paclobutrazol treatment whereas EgGAI gene was not affected by the paclobutrazol application. EgGA20ox gene was constitutively expressed in most tissues tested except for kernel. EgGA2ox gene was highly expressed in young root of the oil palm. On the other hand, EgGAI gene expression was presence in most tissues except for root and kernel. Prior to genes functional study, six expression constructs were generated consisting of three overexpression (pH2OE-EgGA20ox, pH2OE-EgGA2ox, pH2OE-EgGAI) and three RNAi (pH7RNAi-EgGA20ox, pH7RNAi-EgGA2ox, pH7RNAi-EgGAI) constructs. The constructs were transformed into Arabidopsis via Agrobacterium-mediated transformation using floral dip method. Phenotypic characterization analysis of the transgenic Arabidopsis showed that EgGA20ox gene promotes vegetative and reproductive growth. Up regulation of EgGA20ox gene increased the height of transgenic Arabidopsis and length of leaf, root and silique. Flower formation of this line was also improved. Down regulated of EgGA20ox gene reduced the height of Arabidopsis and the length of leaf, root and silique. In addition, less flower formation was observed. On the contrary, up regulation of EgGA2ox gene reduced Arabidopsis height, increased leaf length and delayed in flowering. It was found that there was no effect in terms of flower formation, root and silique. Down regulation of EgGA2ox gene generated taller transgenic Arabidopsis, increased root and leaf length, early flowering but produced normal flower and silique formation. Transgenic Arabidopsis lines carrying oil palm GA-Insensitive (EgGAI) gene were also affecting the vegetative and reproductive growth. Overexpressed of EgGAI gene in transgenic Arabidopsis resulted in shorter plant and reduced root and leaf length. Delayed in flowering was also observed however there was no effect on flower and silique formations. Down regulation of EgGAI gene increased the transgenic Arabidopsis height but reduced the root and leaf length. In terms of reproductive growth, fewer flowers were generated but silique length remain similar to control plant. Based on our findings, EgGA20ox, EgGA2ox and EgGAI genes may play an important role in the plant growth and development. This study has shown that Arabidopsis can be utilized for gene functional studies especially genes involve in oil palm height regulation.